2019
DOI: 10.3390/nu11091973
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the TAS2R38 Bitterness Receptor Gene Was Associated with Food Consumption and Obesity Risk in Koreans

Abstract: Bitterness-sensing protein taste receptor type-2 member 38 (TAS2R38, T2R38) mediates taste perception and various physiological responses, including energy- and adiposity-related mechanisms. This study examined whether the genetic variant rs10246939 C > T in TAS2R38 was associated with food intake and body size as well as obesity risk. Data from the Korean Multi-Rural Communities Cohort study (1338 males and 2229 females) were analyzed to obtain the intake of six food groups, alcohol consumption, smoking statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 52 publications
2
30
1
Order By: Relevance
“…Associations between TAS2R38 genotypes and BMI and associated taster status and BMI have previously been reported [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 41 ]. However, this study is unique in examining the relationship between TAS2R4 and TAS2R5 genotypes and BMI and supports a role for TAS2R genotypes in predicting BMI in males.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Associations between TAS2R38 genotypes and BMI and associated taster status and BMI have previously been reported [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 41 ]. However, this study is unique in examining the relationship between TAS2R4 and TAS2R5 genotypes and BMI and supports a role for TAS2R genotypes in predicting BMI in males.…”
Section: Discussionmentioning
confidence: 95%
“…A potential role for other extra-oral bitter receptors genotypes in predicting BMI has previously been suggested [ 35 , 41 ]. A Korean study ( n = 3567) identified that the TAS2R38 -rs10246939 TT genotype (associated phenotypically with non-tasting) was associated with a significantly higher BMI in females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, studies have attempted to investigate the genetic factors associated with vegetable consumption because consuming a sufficient amount of vegetables is important because they are not only a great source of dietary fibre but are also high in nutritive compounds (46) . The TAS2R38 diplotype was known to be associated with cruciferous vegetable consumption in studies, but this association is still inconclusive in Koreans (47)(48)(49) . The present findings suggest that the potential effect of CD36 genetic variation, not TAS2R38, is associated with vegetable intake in obese males.…”
Section: Discussionmentioning
confidence: 99%